(untitled) (TAJ: Journal of Teachers Association, 2023)
Background: Indwelling urinary catheters are frequently used in critically ill patients. Approximately 66% of patients in intensive care have a urinary catheter in place. Catheter-associated urinary tract infection (CAUTI) is a significant cause of morbidity and mortality, affecting all ages. Antibiotic resistance is one of the biggest public health challenges of our time. Infection with antibiotic-resistant bacteria has become an increasingly complex problem in ICU. Objective: To identify catheter-associated uropathogens and their antimicrobial susceptibility pattern by VITEK2 automated system in intensive care unit patients in Rajshahi Medical College Hospital. Material and Method: A cross-sectional descriptive study was conducted in the Microbiology department of Rajshahi Medical College, the Intensive Care Unit of Rajshahi Medical College Hospital, and a commercial laboratory in Rajshahi during the period of January 2021 to December 2021. The specimen (urine) was inoculated in blood agar, nutrient agar, and MacConkey’s agar media and incubated aerobically at 37˚C for 24 hours. Bacterial isolations and susceptibility tests were done by VITEK2 automated system. Result: Out of the total 96 samples, culture yielded growth was 36 (37.50%), and culture-negative cases were 60(62.50%). In all age groups, males were predominant, totaling 63 (66.20%). A maximum of 33 cases were found in the age group of 18-30 years where males 23(69.70%) and females 10(30.30%). Among the culture-positive isolates, gram-negative organisms were higher (87.17%) than gram-positive (12.82%). Among 39 isolates, Escherichia coli was the predominant organism of 12(30.76%). Other isolates were Klebsiella spp. 10(25.64%), Pseudomonas spp. 5(12.82%), Acinetobacter spp. 4(10.25%), Enterobacter spp. 2(05.12%), CoNS 3(07.69%) respectively. Regarding the antimicrobial susceptibility test, gram-negative organisms were highly susceptible to Colistin, followed by Ertapenem, Imipenem, Meropenem, and Amikacin. The most effective drugs for Gram-positive were Linezolid. Other susceptible drugs against Gram-positive bacteria were Vancomycin and Tigecycline. Conclusion: Most of the isolated bacteria are multidrug resistant. Determining antimicrobial susceptibility by VITEK2 will aid the physician in choosing appropriate antibiotics and treating multidrug-resistant cases. TAJ 2022; 35: No-2: 43-49